2014
DOI: 10.1002/2013ja019442
|View full text |Cite
|
Sign up to set email alerts
|

Substorm onset process: Ignition of auroral acceleration and related substorm phases

Abstract: The substorm onset process was studied on the basis of the vertical evolution of auroral acceleration regions derived from auroral kilometric radiation (AKR) spectra and Pi pulsations on the ground. The field-aligned auroral acceleration at substorm onset demonstrated two distinct phases. Low-altitude acceleration (h~3000-5000 km), which accompanied auroral initial brightening, prebreakup Pi2, and direct current of ultralow frequency (DC-ULF) pulsation were first activated and played an important role (precond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 78 publications
(152 reference statements)
5
10
0
Order By: Relevance
“…This means that low-amplitude highfrequency ULF waves cannot be visually identified without analysis at least on a logarithmic scale. One interesting aspect, however, is the assertion by Morioka et al [2014] that 40-50 s period ULF waves are the signature of a magnetotail instability, which is entirely consistent with the results presented in this chapter. Moreover, we do not limit ourselves to a narrow frequency band; we use instead a broader frequency range that overlaps both the long-period Pi1 and short-period Pi2 bands, since there is no physical distinction between ULF waves of 30 s and 50 s periods, other than the artificial boundary at 40 s initially identified by Jacobs et al [1964] as a matter of practicality.…”
Section: Azimuthal Auroral Forms As Measured By the Themis Asissupporting
confidence: 89%
See 4 more Smart Citations
“…This means that low-amplitude highfrequency ULF waves cannot be visually identified without analysis at least on a logarithmic scale. One interesting aspect, however, is the assertion by Morioka et al [2014] that 40-50 s period ULF waves are the signature of a magnetotail instability, which is entirely consistent with the results presented in this chapter. Moreover, we do not limit ourselves to a narrow frequency band; we use instead a broader frequency range that overlaps both the long-period Pi1 and short-period Pi2 bands, since there is no physical distinction between ULF waves of 30 s and 50 s periods, other than the artificial boundary at 40 s initially identified by Jacobs et al [1964] as a matter of practicality.…”
Section: Azimuthal Auroral Forms As Measured By the Themis Asissupporting
confidence: 89%
“…Morioka et al hypothesized that the increase in ULF wave amplitudes at auroral latitudes during expansion phase onset may instead be related to new acceleration regions developing at high altitudes in the magnetosphere-ionosphere coupling region, not the inner plasma sheet. From this, Morioka et al [2014] conclude that the magnetic Pi2 waves (40-50 s period) observed are likely a signature of a magnetospheric instability, whereas the Pi1 waves (10-30 s period) are a signature of intensified FACs in conjugate M-I coupling regions. Although Morioka et al [2014] provide compelling evidence that the AKR generation during substorms is a two-step process, it is necessary to question the ULF data more deeply.…”
Section: Azimuthal Auroral Forms As Measured By the Themis Asismentioning
confidence: 81%
See 3 more Smart Citations